2014
DOI: 10.1186/s13059-014-0551-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide modulation of splicing by the exon junction complex

Abstract: BackgroundThe exon junction complex (EJC) is a dynamic multi-protein complex deposited onto nuclear spliced mRNAs upstream of exon-exon junctions. The four core proteins, eIF4A3, Magoh, Y14 and MLN51, are stably bound to mRNAs during their lifecycle, serving as a binding platform for other nuclear and cytoplasmic proteins. Recent evidence has shown that the EJC is involved in the splicing regulation of some specific events in both Drosophila and mammalian cells.ResultsHere, we show that knockdown of EJC core p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 72 publications
12
61
0
Order By: Relevance
“…Depletion of the EJC proteins causes changes in splicing patterns in Drosophila and other organisms (Ashton-Beaucage et al, 2010; Hayashi et al, 2014; Malone et al, 2014; Michelle et al, 2012; Roignant and Treisman, 2010; Wang et al, 2014). These changes can be interpreted in two ways: either canonical EJC deposition can influence splicing of neighbouring introns or the EJC proteins can affect splice site recognition by being functional components of pre-spliceosome intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of the EJC proteins causes changes in splicing patterns in Drosophila and other organisms (Ashton-Beaucage et al, 2010; Hayashi et al, 2014; Malone et al, 2014; Michelle et al, 2012; Roignant and Treisman, 2010; Wang et al, 2014). These changes can be interpreted in two ways: either canonical EJC deposition can influence splicing of neighbouring introns or the EJC proteins can affect splice site recognition by being functional components of pre-spliceosome intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic studies in mammalian cells further support a global function for core EJC components in mRNA splicing (Wang et al, 2014). Wang et al (2014) observed splicing defects with knockdown of EIF4A3, RBM8A and CASC3 in HeLa cells. The observation that CASC3 influences splicing in human cells but not Drosophila, could be due to species or cell specific differences.…”
Section: Introductionmentioning
confidence: 93%
“…Splicing regulation is thought to occur via mechanisms in which EJCs define and influence the splicing of neighboring introns (Hayashi et al, 2014). Genomic studies in mammalian cells further support a global function for core EJC components in mRNA splicing (Wang et al, 2014). Wang et al (2014) observed splicing defects with knockdown of EIF4A3, RBM8A and CASC3 in HeLa cells.…”
Section: Introductionmentioning
confidence: 99%
“…This default is meant to provide a reasonably stringent baseline. The RNA-seq data for eIF4A3, described in Wang et al (2014), were downloaded from GEO (GSE63091) and data were analyzed similarly to Acinus RNA-seq data. Significant events detected in Acinus or eIF4A3 RNA-seq were compared as described below.…”
Section: Splicingmentioning
confidence: 99%